2009
DOI: 10.1038/sj.bjc.6605190
|View full text |Cite
|
Sign up to set email alerts
|

Tumour growth and resistance to gemcitabine of pancreatic cancer cells are decreased by AP-2α overexpression

Abstract: BACKGROUND: Activator protein-2a (AP-2a) is a transcription factor that belongs to the family of AP-2 proteins that have essential roles in tumorigenesis. Indeed, AP-2a is considered as a tumour-suppressor gene in different tissues such as colonic, prostatic or breast epithelial cells. Moreover, AP-2a also participates in the control of colon and breast cancer cells sensitivity towards chemotherapeutic drugs. Despite its potential interest, very few data are available regarding the roles of AP-2a in pancreatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 24 publications
1
35
0
Order By: Relevance
“…Cited2 has also been shown to regulate the expression of the cell cycle inhibitor p57 in hematopoietic stem cells, and p57 levels are decreased in the Cited2 knockout mouse (20,21). Furthermore, TFAP2 overexpression results in increased p57 expression (55). Consistent with the findings above, we showed that depletion of Cited2 results in decreased p57 expression, leading to increased cell cycle activity and cardiomyocyte proliferation.…”
Section: Discussionsupporting
confidence: 80%
“…Cited2 has also been shown to regulate the expression of the cell cycle inhibitor p57 in hematopoietic stem cells, and p57 levels are decreased in the Cited2 knockout mouse (20,21). Furthermore, TFAP2 overexpression results in increased p57 expression (55). Consistent with the findings above, we showed that depletion of Cited2 results in decreased p57 expression, leading to increased cell cycle activity and cardiomyocyte proliferation.…”
Section: Discussionsupporting
confidence: 80%
“…Irrelevant rabbit or mouse IgG was used as a negative control. Western blotting was performed as described in Jonckheere et al (2009). The membrane was probed with an anti-phospho-EGFR, anti-EGFR or anti-MUC1 (m8) antibody.…”
Section: Immunoprecipitationmentioning
confidence: 99%
“…Pancreatic cancer is a leading cause of cancer-related death in the world and is characterized by rapid disease progression, highly invasive tumor phenotype, and resistance to chemotherapy [1,2]. Despite significant advances in diagnosis, staging, and surgical management of the disease, overall 2 years survival in US, Europe, Australia is around 20%, and 50-70% of patients may survive 2 years if treated with chemotherapy and surgery [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Despite significant advances in diagnosis, staging, and surgical management of the disease, overall 2 years survival in US, Europe, Australia is around 20%, and 50-70% of patients may survive 2 years if treated with chemotherapy and surgery [1,2]. Chemotherapy is the primary treatment option for most patients with pancreatic cancer, but the standard agents, such as fluorouracils (5-FU), capecitabine, and gemcitabine have had limited impact on patient survival [1,2]. Thus, the search for more effective chemotherapeutic agents is still ongoing, and new regimens are under active investigation.…”
Section: Introductionmentioning
confidence: 99%